Developing the concept of leaveism: From presenteeism/absence to an emergent and expanding domain of employment?. (23rd May 2022) - Richards, James; Ellis, Vaughan; Canduela, Jesus; Pustelnikovaite, Toma; Saxena, Siddhartha
Abstract: The changing nature of employment has led to increased awareness of leaveism, a practice involving employees using allocated time off when unwell, taking work home, and picking up work when on annual leave. However, there are theoretical, methodological, and policy/practice‐related weaknesses, apparent in current understandings. The main article aim is to develop, theoretically, the emergent notion of leaveism, drawing on concepts related to work intensification (WI) and ideal worker norms (IWNs), concepts underpinned by reference to information communication technologies (ICTs), then exploring such ideas via an electronic questionnaire ( n = 959), aimed at UK‐based employees performing leaveism. The main argument is leaveism is more than a lacuna between presenteeism and sickness absence; it is an unsustainable employer‐driven social phenomenon sitting at the intersection of WI, IWNs and ICTs. The findings have policy/practice implications for human resource management (HRM) professionals, trade unions and governments. Recommendations for future research including exploring leaveism in an international context, and in a Covid‐19 pandemic‐defined era.